Analysis of dye-sensitized solar cells based on ZnO and ZnO–Ni photoanodes with various Ni concentrations - Abdullah, H.; Xian, K. J.; Ying, K. C.; Naim, N. M.; Akhtaruzzaman, M.; Berhanuddin, D. D.; Keng, L. K.; Rizwan, M.; Othman, M. H.D.; Ahmad, M. F.; Fen, Y. W.; Jannah, A. N. (Pleiades Publishing, 2024)
Abstract: In recent years, ZnO nanostructure thin films have been used extensively by researchers in dye-sensitized solar cells (DSSCs) application due to its unique photovoltaic properties. The effects of the concentrations of Ni metal dopants on ZnO thin film DSSCs were investigated. ZnO–Ni nanocomposites were synthesized via sol-gel method. In this paper, the structural, morphological, and chemical properties of ZnO–Ni nanocomposite thin films were reported. Field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), atomic force microcopy (AFM) and mapping analyses have found out that the crystallite and grain sizes of ZnO-Ni is increasing when Ni percentage is increased. The optical study from UV-Vis spectroscopy indicates that the band gap energy for ZnO–Ni photoanodes is in the range 3.5–3.7 eV. Energy dispersion X-ray (EDX) and X-ray photoelectron spectroscopy (XPS) have identified the elements and chemical bonding that are related to ZnO and Ni. The photovoltaic performances were analyzed using photocurrent-voltage (J–V) measurement and electrochemical impedance spectroscopy (EIS). As the result, ZnO–Ni photoanode based DSSC with 60% of Ni concentration shows the highest power conversion efficiency (0.421%) with Jsc, Voc and FF of 1 mA/cm2, 0.95 V and 0.443. © Allerton Press, Inc. 2024. ISSN 0003-701X, Applied Solar Energy, 2024, Vol. 60, No. 3, pp. 461–472. Allerton Press, Inc., 2024.